Exploring Requisite Competency Profiles for an Automated Cement Factory: A Study of Selected Robolab Cement Factories in South Africa: Array - Manganye, Annah; Mbukanma, Ifeanyi (Acta Universitatis Danubius. Œconomica, 2020)
The technological innovations in the cement manufacturing industries has grown in recent time from the conventional methods (where manual skills were majorly used) to an automated Robolab system. The Robolab system however, comes with its own difficulties as the process of operating it requires competent professionality. Thus, this study was carried out on this context to exploit the requisite competencies that are required for optimal operation of the Robolab system to maximize cement product and minimize human errors. To achieve this objective, a qualitative research method was adopted, which provided an ample approaches that help in addressing the research objective of this study. A qualitative data was collected from Robolab operators as well as employers of selected cement production factories in South Africa. A thematic method of data analysis was employed to analyse the qualitative data that was gathered through interview questions. The findings of the study revealed that requisite competencies such as technical, behavioural, professional, innovative and creative competencies are key for optimal operation of Robolab system in a cement production factory. Hence, it was recommended that stakeholder within the Robolab cement production factories in South Africa should employ the Integrated Robolab Competency-Profiling Model, which advocates for competency literacy among the employers and users of Robolab system.